Embodied, Embedded, and Enactive Psychopathology Reimagining Mental Disorder - Nielsen, Kristopher (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
Embodied, Embedded, and Enactive Psychopathology presents a new way of thinking about mental disorder that is holistic yet critically minded, biologically plausible yet value-inclusive, and scientific yet deeply compassionate. Grounded in an embodied, embedded, and enactive (3e) view of human functioning, this book presents a novel conceptual framework for the study and treatment of mental disorders and explores implications for the tasks of classification, explanation, and treatment. Chapters one to three argue for the central role of conceptualization in the study and treatment of mental disorders. Popular conceptual models are critiqued, including other recent enactive frameworks. Chapters four to seven then present 3e Psychopathology and explore its implications. This includes analysis of both research-based efforts to explain mental disorders, and methods for formulating individual-level explanations in clinical practice. New answers are presented for important questions such as: are mental disorders things we do or get? Are mental disorders defined in nature or are they socially constructed? Are mental disorders the same things across different cultures? And, are mental disorders located in our brains, bodies, or environments? This engaging work offers fresh insights that will appeal to clinicians, researchers, and those with an interest in the philosophy of psychiatry. .
Chapter 1- Conceptualization as a Core Scientific Task -- Chapter 2- Current Conceptual Models -- Chapter 3- Previous Enactive Views of Mental Disorder -- Chapter 4- The Bones of a New Perspective -- Chapter 5- 3e Psychopathology: A New Perspective and Questions of Classification -- Chapter 6- How Then Should We Explain? -- Chapter 7- How Then Should We (Begin to) Treat? -- Chapter 8- Summing Up and Moving Forward. .
Keywords: Psychology, Pathological; Mental health; Psychiatry; Philosophy of mind; Knowledge, Theory of; Psychopathology; Mental Health; Psychiatry; Philosophy of Mind; Epistemology